السعادة النفسية وعلاقتها بالتدفق النفسي لدى تلاميذ السنة ثالثة ثانوي - جبالي, أمال; دبيلي, نوال (University of Eloued جامعة الوادي, 2023)
الملخص: هدفت الدراسة الحالية إلى التعرف على السعادة النفسية وعلاقتها بالتدفق النفسي لدى تلاميذ السنة ثالثة ثانوي وتحديد الفروق في ضوء متغير الجنس والتخصص الدراسي وقد طرحت الدراسة تساؤلاتها على النحو التالي: - هل توجد علاقة دالة احصائيا بين درجات السعادة النفسية ودرجات حالة التدفق النفسي لدى تلاميذ السنة ثالثة ثانوي. - هل توجد فروق دالة احصائيا بين متوسطات السعادة النفسية لدى تلاميذ السنة ثالثة ثانوي حسب متغير التخصص(علوم تجريبية/تقني رياضي/آداب/تسيير؟ واقتصاد)؟ - هل توجد فروق دالة احصائيا بين متوسطات حالة التدفق النفسي لدى تلاميذ السنة ثالثة ثانوي حسب متغير الجنس؟ ولتحقيق هاته الدراسة تم الاعتماد على المنهج الوصفي من خلال الإستعانة بمقياس السعادة ومقياس التدفق النفسي وقد طبقت هاته المقاييس على عينة قوامها 81 تلميذ وتلميذة بثانوية المجاهد إبراهيم شرفي بسيدي عون، وقد اختيرت بطريقة عشوائية وقد أسفرت نتائج هاته الدراسة كالتالي: - توجد علاقة دالة احصائيا بين درجات السعادة النفسية ودرجات حالة التدفق النفسي لدى تلاميذ السنة ثالثة ثانوي. - توجد فروق دالة احصائيا بين متوسطات السعادة النفسية لدى تلاميذ السنة ثالثة ثانوي حسب متغير الجنس. - توجد فروق دالة احصائيا بين متوسطات حالة التدفق النفسي لدى تلاميذ السنة ثالثة ثانوي حسب متغير الجنس. - توجد فروق دالة احصائيا بين متوسطات السعادة النفسية لدى تلاميذ السنة ثالثة ثانوي حسب متغير التخصص(علوم تجريبية/تقني رياضي/آداب/تسيير واقتصاد). - توجد فروق دالة احصائيا بين متوسطات حالة التدفق النفسي لدى تلاميذ السنة ثالثة ثانوي حسب متغير التخصص(علوم تجريبية/تقني رياضي/آداب/تسيير واقتصاد ). وقد تم تفسير نتائج الدراسة بناءً على الخلفية النظرية للدراسة وبعض الملاحظات المستقاة من الميدان . Abstract : The current study aimed to identify psychological happiness and its relationship to psychological flow among third year secondary school students, and to identify differences in the light of the variable of gender and academic specialization. The study raised its questions as follows: - Is there a statistically significant relationship between the degrees of psychological happiness and the degrees of psychological flow among third year secondary school students? - Are there statistically significant differences between the averages of psychological happiness among third year secondary school students according to the specialization variable (experimental sciences / mathematical technology / literature / management? and economics(? - Are there statistically significant differences between the averages of the state of psychological flow among third year secondary school students according to the gender variable? To achieve this study, the descriptive approach was relied on by using the happiness scale and the psychological flow scale. These measures were applied to a sample of 81 male and female students at the Mujahid Ibrahim Charfi High School in SidiAoun, and they were chosen randomly. The results of this study were as follows: - There is a statistically significant relationship between the degrees of psychological happiness and the degrees of the state of psychological flow among third year secondary school students. - There are statistically significant differences between the averages of psychological happiness among third year secondary school students according to the gender variable. - There are statistically significant differences between the averages of the state of psychological flow among third year secondary school students according to the gender variable. - There are statistically significant differences between the averages of psychological happiness among third year secondary school students according to the specialization variable (experimental sciences / mathematical technology / literature / management and economics( - There are statistically significant differences between the averages of the state of psychological flow among third year secondary school students according to the specialization variable (experimental sciences / mathematical technology / literature / management and economics( The results of the study were interpreted based on the theoretical background of the study and some observations drawn from the field
دراسة ميدانية بثانوية - المجاهد شرفي ابراهيم - بسيدي عون
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: السعادة النفسية، le bonheur psychologique, psychological happiness; التدفق النفسي، flux psychologique, psychological flow